Phytotherapy, allium sativum and hypercholesterolemia: a review - da Silva, Paloma Legal; Silva, Everaldo Morais; do Carmo, Maria das Graças Tavares; Cardoso, Felipe de Souza (Journal of Health Care, 2016)
Introduction: Currently, chronic diseases are considered major public health problem. In Brazil, the main cause of death is due to coronary artery disease. Among the risk factors, cholesterol has been pointed out, both observational and experimental preclinical and clinical evidence, as the main modifiable risk factor. The objective of this review study was to evaluate the action of Allium sativum species on the lipid profile of adults with dyslipidemia. Development: conducted a literature review in the following databases: SciELO and PubMed. English language following keywords: "Allium sativum", "hypercholesterolaemia", "dyslipidemia", "cardiovascular diseases" and "chronic diseases". The study prioritized items between the years 1993 and 2014, not excluding items considered classics. The sample size of the research evaluated Allium sativum ranged from 15 to 192, indicating from raw form to standardized extract, and dose ranging between 5 and 7200 mg total garlic. Despite methodological limitations observed as oscillations between doses, presentations and small sample, 58% approximately indicated benefits of using garlic over control of the lipid profile, particularly with regard to total cholesterol changes and lipoprotein low density, suggesting that the allicin substance present in the quantity of raw garlic powder or total extract would be the main modulator of the observed effects on the lipid profile. It was observed that the reduction of total cholesterol varies between 4.2 and 12.1%, and the variation in reducing low density lipoprotein between 6.6 and 17.6%. Conclusion: Allium sativum appears to be a safe and effective alternative for reducing hypercholesterolemia. However, research demonstrating clinical evidence is necessary to exclude possible confounding variables.
Keywords: allium sativum; hypercholesterolaemia; dyslipidemia; cardiovascular diseases; chronic diseases